The effect of metacognition and self‐directed learning readiness on learning performance of nursing students in online practice classes during the COVID‐19 pandemic period - Sanghee Kim (Wiley, 2024)
Abstract Aim This study was a descriptive correlation investigation to determine the effects of metacognition and self‐directed learning readiness on learning performance of nursing students in online practice classes during the COVID‐19 pandemic. Design and Methods In this descriptive cross‐sectional study, 135 subjects were randomly selected from junior students of one university in South Korea. Results In this study, metacognitive knowledge in nursing students showed a positive relationship with subjective learning performance (r = 0.34, p = 0.002) and objective learning performance (r = 0.38, p = 0.016). Metacognitive control in nursing students also showed a positive relationship with subjective learning performance (r = 0.37, p = 0.001) and objective learning performance (r = 0.41, p < 0.001). Self‐directed learning readiness in nursing students showed a positive relationship with subjective learning performance (r = 0.38, p = 0.011) and objective learning performance (r = 0.40, p < 0.001). Conclusion For effective online practical education, nursing students' internal characteristics of metacognition and self‐directed learning should be identified in advance, and schools should strive to help nursing students' learning performance by developing and applying education systems or contents.